Honey characterization and identification of fructophilic lactic acid bacteria of fresh samples from Melipona beecheii, Scaptotrigona pectoralis, Plebeia llorentei, and Plebeia jatiformis hives - Andrade-Velásquez, Amaury; Hernández Sánchez, Humberto; Dorantes-Álvarez, Lidia; Palmeros-Sánchez, Beatriz; Torres-Moreno, Raymundo; Hernández-Rodríguez, Dolores; Melgar-Lalanne, Guiomar (Frontiers in Sustainable Food Systems, 2023)
Stingless bees are essential to preser tropical ecosystems. They pollinate native flora, producing honey with properties for traditional health uses. Lactic acid bacteria spontaneously ferment honey in stingless bee honey (SBH). This study aims to determine the main physicochemical characteristics of Melipona beecheii, Scraptotrigona pectoralis, Plebeia jatiformis and Plebeia llorentei honey and to isolate and identify FLAB present in SBH samples. The physicochemical properties of SBH, such as color, pH, acidity, sugars, protein, total soluble solids, water activity, total polyphenols, and antioxidant activity, were determined since these parameters can be related to the presence of some bacteria groups, and with health benefits for humans and the hive ecosystems. FLAB harvested from honey, taken directly from storing pots of the hives, were identified by 16S ribosomal RNA sequencing and preserved for future biotechnological use due to their resistance to non-ionic osmotic stress. The results showed significant differences in the physicochemical characteristics of SBH samples. Seven FLAB from four stingless bee species were identified as Fructobacillus pseudoficulneus and F. tropaeoli. In addition, three other strains of Fructilactobacillus spp. were identified only at the genus level. All species showed the ability to grow under different carbon sources, resulting in negative hemolysis and sensitivity to cefuroxime, erythromycin, and chloramphenicol. To the best of our knowledge, this is the first time that the physicochemical and FLAB characterization of SBH from P. jatiformis and P. llorentei has been reported. Therefore, the future following research should be focused on the environmental, health and food biotechnological applications implications of FLAB from SBH.